Sensitive identification of milk protein allergens using on-line combination of transient isotachophoresis/micellar electrokinetic chromatography and capillary isoelectric focusing in fused silica capillary with roughened part. (30th May 2022) - Horká, Marie; Šalplachta, Jiří; Karásek, Pavel; Roth, Michal
Graphical abstract: Highlights: Milk protein allergens from diluted skimmed milk were concentrated and analysed. Proteins were dynamically adhered from large sample volume onto capillary surface. The FS capillary with nano-structured inner part was used in these experiments. On-line combination of tITP/MEKC with CIEF was used for adhered protein separation. This method allows to detect protein allergens according to their migration time and pI. Abstract: A method for on-line concentration of milk proteins from large sample volumes using combination of transient isotachophoresis (tITP) and micellar electrokinetic chromatography (MEKC) in fused silica capillary with an inner roughened part has been developed. The method utilizes reversible dynamic adsorption of proteins onto a thin layer of PEG 4000 on the roughened surface of the capillary. In addition, the tITP/MEKC method was combined with capillary isoelectric focusing (CIEF) for on-line concentration, separation, identification and sensitive determination of proteins in skimmed milk. The method allows analysis of up to 50 μL of sample. This study has focused on the four important whey proteins, bovine serum albumin (BSA), α-lactalbumin (α-LA), and two genetic variants of β-lactoglobulin (β-LG A and β-LG B). The proteins were identified on the basis of their migration times and characteristic p I values. The p I values of BSA, α-LA, β-LG A, and β-LG B were determined as 4.7, 4.4, 5.1, and 5.2, respectively. Limits of detection for BSA, α-LA and both β-LG variants were found as 1.2, 1.0 and 1.0 pg mL −1, respectively. The linearity of calibration curves was characterized by the R 2 = 0.9982. The method provided highly reproducible results as the relative standard deviations of the migration times and peak areas of the examined proteins did not exceed 1.6%.